Applying the phenomenological approach to educational place: A case study analysis of a college experience through time - Ahmed Ameen Aqeel; Najla Allani (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2023)
Applying the phenomenological approach to architecture relies on integrating human experiences and sensory aspects into the designed space, materials, and light to create a place that has a lasting impact on the memory in the human mind. This experience can change if the person experiences the space at a different time. This case study focuses on some students' sensory experiences of the College of Engineering at the University of Bahrain who attended the College during their academic years and then visited it after a long detachment period. This study relies on interviews with the students focusing on their previous and actual college experience to discover the changes in the experience of the same space through different times. The promising results showcase that mental images have changed, and students' attachment has become more substantial due to detachment and time.